2020
DOI: 10.4252/wjsc.v12.i10.1097
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-based therapies for fertility preservation in males: Current status and future prospects

Abstract: With the decline in male fertility in recent years, strategies for male fertility preservation have received increasing attention. In this study, by reviewing current treatments and recent publications, we describe research progress in and the future directions of stem cell-based therapies for male fertility preservation, focusing on the use of spermatogonial stem cells (SSCs), SSC niches, SSC-based testicular organoids, other stem cell types such as mesenchymal stem cells, and stem cell-derived extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 212 publications
(199 reference statements)
0
5
0
Order By: Relevance
“…Moreover, the LCs in the organoids possessed endocrine functionality and LH responsiveness. FSH was also shown to increase the levels of Inhibin b, which may be an important factor in the self-renewal of SSCs [35]. These data demonstrate that our organoids can sustain long-term and durable endocrine function with preserved gonadotropin responsiveness, providing an effective model for studying testis endocrine function in vitro.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, the LCs in the organoids possessed endocrine functionality and LH responsiveness. FSH was also shown to increase the levels of Inhibin b, which may be an important factor in the self-renewal of SSCs [35]. These data demonstrate that our organoids can sustain long-term and durable endocrine function with preserved gonadotropin responsiveness, providing an effective model for studying testis endocrine function in vitro.…”
Section: Discussionmentioning
confidence: 52%
“…Similar to MSC Exos, Exos isolated from induced pluripotent stem cells (iPSCs) could recover testicular function and support protective signals against damaged spermatogenesis. [90] Phosphorylation of tyrosine residues is a critical event that can control the activity of sperms and thus the fertility rate. It was found that seminal plasma Exos can phosphorylate tyrosine to improve sperm capacitation and acrosomal reaction.…”
Section: Therapeutic Effects Of Exos On the Reproductive Systemmentioning
confidence: 99%
“…Similar to MSC Exos, Exos isolated from induced pluripotent stem cells (iPSCs) could recover testicular function and support protective signals against damaged spermatogenesis. [ 90 ]…”
Section: Therapeutic Effects Of Exos On the Reproductive Systemmentioning
confidence: 99%
“…Currently, there are not many references that exclude the possibility of reoccurrence of cancer by autotransplantation, thus re-implantation strategies for real-time clinical application are still under study. SSC cells are maintained in their natural niche and can only be proposed if the presence of tumor cells is excluded (Liu et al 2020). Xenografts have shown full spermatogenesis in several animal species but never in humans (Goossens et al 2008).…”
Section: Nanotechnology and Sperm Lifementioning
confidence: 99%